(untitled) (SAARC Journal of Agriculture, 2023)
Crop rotations have always a vital role in balancing of inter crops nutritional management, inhibiting of soil degradation, reduction of biotic and a biotic stress and in adapting to climate change. Potohar region is divided into three distinct rainfall zones i.e. high rainfall (>750 mm of annual rainfall), medium (500 to 750 mm) and low rainfall (<500 mm). Wheat is main rabi season crop of this region, while during kharif season groundnut, maize and sorghum are mostly planted in some areas, however maximum area is kept fallow and farmers plough it up for a number of times to conserve rain water for the planting of wheat crop. During two different crop seasons (2014-15 and 2016-17), adaptation plots of Mungbean-Wheat cropping system in comparison with Fallow-Wheat cropping system were planted on five different farmer’s fields, in the medium and high rainfall zones of this region. During both years yields of both Mungbean and wheat crop varied from field to field, especially due to rainfalls timings and their quantities, soil conditions, cropping systems and crop management etc. During cropping seasons 2014-15 and 2016-17, wheat crop grain yields were recorded 3.80 t/ha and 2.92 t/ha respectively in Mungbean - Wheat cropping system as compared with Fallow-Wheat cropping system having yields of 3.15 t/ha and 2.85 t /ha respectively. Overall results show that Mungbean-Wheat cropping system is not only economically better but is also soil health and environment friendly. It can also be helpful in the promotion of climate smart agriculture in this region. SAARC J. Agric., 21(2): 95-107 (2023)